AN ANALYSIS ON THE ROLE OF STOCK BROKERAGE HOUSES IN COMMUNITY DEVELOPMENT - Beg, Tahrima Haque; Afrina, Taskin; Hridoy, Miftahul; Hossen, Md. Abir; Hossain, Rashel (American International Journal of Multidisciplinary Scientific Research, 2024)
This study investigates the role of stock brokerage houses in community development within the context of Bangladesh's capital market. Data and information are sourced from a variety of secondary sources, encompassing financial platforms like the Dhaka Stock Exchange (DSE) and Chittagong Stock Exchange (CSE), credible news websites such as Investing.com, published literature, and official reports from regulatory authorities such as the Bangladesh Bank and the Bangladesh Securities and Exchange Commission (BSEC). Quantitative data spanning the period from 2010 to 2019 are meticulously extracted from stock exchange databases as well as the IMF World Economic Outlook database. These datasets are meticulously structured and analyzed using tables, charts, and graphs. Amidst challenges such as market collapses and the COVID-19 pandemic, the resilience and growth of Bangladesh's capital market are evaluated. The results reveal that brokerage houses have a significant impact on community development in Bangladesh. For instance, the total traded volume reached Tk. 2,169,597 million in 2017, marking an 82.08% increase from the previous year. Sector-wise turnover data showed consistent investment trends, particularly in manufacturing, financials, and pharmaceuticals. These investments have led to job creation and infrastructure development, highlighting the role of brokerage houses in fostering employment and socioeconomic advancement. Additionally, the adoption of online trading platforms has driven technological advancement and financial inclusion. The findings of this study suggest that brokerage houses are crucial intermediaries in the capital market, contributing to economic growth, financial inclusion, and community development through their investment activities and corporate social responsibility initiatives.JEL Classification Codes: G20, G23, O16, R51.